PENGARUH MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VIII UPTD SMP NEGERI 3 PEMATANGSIANTAR - Andreas Siagian; Benjamin Albert Simamora; Binsar Tison Gultom (JURNAL ILMIAH NUSANTARA, 2024)
The results of the study stated that: 1) Financial literacy has a significant effect on students' consumer behavior. This result can be seen in the t-test where the t-count value of financial literacy (3.683) > t-table value (1.291) and the significant value obtained by financial literacy is 0.000 < 0.1. 2) Lifestyle has a significant effect on students' consumer behavior. This result can be seen in the t-test where the t-count value is (2.726) > t-count value (1.291). The significant value obtained by lifestyle is 0.008 < 0.1. 3) Financial Literacy and Lifestyle have a significant effect on consumer behavior. This result can be seen in the F-test where the F-count value is 17.459> from F-table with df = n-k-1 (92-2-1) of 2.36. The determination coefficient test R Square is known to be 0.282 which means 28.2% of financial literacy and lifestyle on student consumptive behavior and 71.8% is the influence of other variables not examined in this study.